E-065 Diagnosis and management of intracranial hypotension: a case review. (4th July 2012) - Bourgeois, A; Kvamme, P; Chang, T; Laing, G
Abstract : Purpose: Headache remains one of the top three most common indications for neurologic imaging. Intracranial hypotension is one causative etiology of headache, which although rare, carries considerable morbidity and potential mortality. Initial misdiagnosis is very common despite the presence of a unique and well-defined constellation of imaging findings. This case-based review examines the mechanisms of pathogenesis, common clinical features, and imaging findings associated with seven recent cases of intracranial hypotension. Interventional management of symptomatic intracranial hypotension includes epidural blood patching, percutaneous placement of fibrin sealant, and surgical CSF leak repair. However, outcomes and treatment strategies remain poorly studied. This review also discusses various treatment strategies utilizing our own experience, in order to better manage intracranial hypotension. Methods: Following IRB approval, a retrospective chart review was performed from the time period of January 1, 2009–October 1, 2011. Symptomatic patients with low intracranial pressures (<15 cm H2 O) as demonstrated by lumbar puncture and with correlating cross sectional imaging within 1 month of the diagnostic lumbar puncture were included. Results: Each of the seven patients displayed at least one classic imaging feature of intracranial hypotension: Downward displacement of the brain through the incisura or "slumping of the midbrain". Diffuse dural thickening and enhancement. Venous and dural sinus distension. Subdural hygromas/hematomas. Perineural root sleeve cysts. Epidural contrast collections. Flaring or other bizarre root sleeve morphology. Abnormal nerve root morphology and epidural fluid/contrast collections were the most common imaging abnormalities. CT guided percutaneous, multilevel epidural patching using own blood or synthetic patch material were utilized for treatment. Five of the seven patients required a repeat procedure. Conclusion: Recognition of the common findings of intracranial hypotension is important as this diagnosis is often not considered, potentially leading to more invasive and ineffective therapies. When detected, successful treatment can be achieved utilizing several techniques although repeat treatments are often necessary. Competing interests: None. References: 1. Rabin, Barry, et al. Spontaneous intracranial hypotension: spinal MR findings. Am J Neuroradiol 1998;19 :1034–9. 2. Farb RJ, et al. The venous distension sign: a diagnostic sign of intracranial hypotension at MR imaging of the brain. AJNR Am J Neuroradiol 2007;28 :1489–93. 3. Schievink, Wouter. Spontaneous spinal cerebrospinal fluid leaks and intracranial hypotension. JAMA 2006;295 :2286–96. 4. Schievink, Wouter, et al. Diagnostic criteria for spontaneous spinal CSF leaks and intracranial hypotension. Am J Neuroradiol 2008;29 :853–6.